FACTORES QUE AFECTAN EL INTERVALO PARTO-PRIMERSERVICIO YPRIMER SERVICIO-CONCEPCIÓN EN VACAS LECHERAS DEL VALLE DELMANTARO DURANTE LAÉPOCALLUVIOSA - Arana D., Carlos (2012)
A reproductive study was conducted in the El Mantaro valley, Junín, Peru. Forty milking cows from 6 farms were monitored during the rainy season. The effect of breed, parity, milk yield, farm, and technological level on the interval fromcalving to first ovulation (CFOI), to first service (CFSI), and to conception (CCI) were evaluated. CFOI was determined through progesterone radioimmunoassayconcentration in defatted milk.CFOI was within the expected range for dairy cattle (41.2 ± 20.2 days); however, CFSI (118.4 ± 69.2) and CCI (171.3 ± 105.5 days) were too long, possibly due to heat detection failures and nutritional constraints. Farm technological level was the only variable of importance that affected CFSI.